COMPARATIVE EFFICIENCY AND SAFETY APPRAISAL OF TWO VACCINES AGAINST TYPE B HEMOPHILIC INFECTION: ACT_HIB AND HIBERIX AMONG CHILDREN - V.V. Botvin'eva; L.S. Namazova-Baranova; A.G. Gaivoronskaya; E.G. Filyanskaya; I.Z. Dzhgarkava (Union of pediatricians of Russia, 2009)
The article highlights the results of the research carried out at the department of the vaccine prevention of the Scientific center of children's health RAMS to study the efficiency and safety of vaccination against the type b hemophilic infection (Hib'infection). The authors compared two vaccines applied for the prevention of this infection: Act' Hib and Hiberix. They proved similar efficiency, good tolerance and safety of both vaccines. The authors also made up recommendations for optimized vaccination of the children with different health statuses.Key words: hemophilic infection, vaccination, children.